Bullying as a Risk Factor of Depression on Undergraduate Health Students - Rizky Setiadi BSN., RN., MPH; Arsyawina BAppSc (AdvNurs); Umi Kalsum BEd., MPH; Nursari Abdul Syukur BAppSc (Mid); Iwan Muhamad Ramdan BSN., MHSc., Dr (PH) (SAGE Publishing, 2021)
Depression is a serious health problem that needs to be treated early so that it does not get worse in the future. Bullying can cause a mental health problem on students. This study aims to analyze the relationship between bullying and depression among undergraduate health students. This was an observational study with a cross-sectional design. Respondents filled out questionnaires online using the Google Form application. A total of 246 undergraduate health students participated in this study. Multivariate logistic regression was used to analyse the data. There was a relationship between bullying and the incidence of depression in undergraduate health students (AOR: 2.158 (95% CI: 1.050-4.435)) after being controlled by physical attacked, close friends, loneliness, and smartphone addiction. This study proves that bullying is a risk factor for depression. Prevention of bullying is important to prevent depression. Handling and prevention are done by involving peer support from students through peer-counselor or peer-educator programs. Students with severe depression need to be treated further through an appropriate referral system.